Treatment of Cashback in Income Tax - YERIKHO, GABRIEL; WIJAYA, SUPARNA (The journal of contemporary issues in business and government, 2021)
Further provisions regarding cashback as an expense in calculating income tax have not been regulated explicitly in taxation regulations in Indonesia. This is because the term cashback has just recently appeared. This study aims to understand the treatment of cashbacks in calculating income tax for digital wallet companies. The research method used is descriptive qualitative. The results show that while the application of taxable-deductible principle does not clearly determine cash back as a deductible expense, digital wallet companies may utilize a nominative list for taxation provision. The existence of a nominative list is proof that cashback is not fictitious expense.